REDUKSI STIGMA TERHADAP ORANG DENGAN GANGGUAN MENTAL - Andria Pragholapati; Rinanda Amalia Shaleha; Lina Anisa Nasution; Irma Darmawati (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Stigma is a relational and social process in which negative characteristics are associated with groups/individuals based on prejudice which leads to discriminatory behavior (identifies as being different or undesirable). Stigma plays a role in forming a bad image in mental disorders. The stigma of mental illness causes the person experiencing it to lose self-esteem, prevents them from seeking medical help, and prevents them from getting opportunities such as job opportunities and opportunities to live independently and safely. If the stigma about mental disorders is still developing among the general public and health workers, it will prevent people with mental disorders from getting help. The purpose of this community service activity through the Stigma Reduction Webinar for People with Mental Disorders is to provide education and health campaigns that can reduce stigma against people with mental disorders. Through this service activity, the community is expected to know the impact of stigma and change the negative perception of people with mental disorders.